Evil in emerald - Stuart, A. M., 1959- (A Harriet Gordon mystery, 2022)
"Harriet Gordon joins a local musical theatre production looking for a change of pace, but the brutal killing of a cast member will force her and Inspector Curran to turn the spotlight on murder in this all-new mystery from the author of Revenge in Rubies. Harriet Gordon has been enjoying the rehearsals for her role in the Singapore Amateur Dramatic and Music Society's latest production-Pirates of Penzance. Her work at her brother Julian's school, as well as her job typing up Inspector Robert Curran's police reports, doesn't leave her much time for extra-curricular personal pursuits. But Harriet quickly discovers tensions run deep within the company and when the leading man is found murdered, suspicions abound, exposing not only several scandalous affairs but also widespread fraud that could destroy a prominent businessman. Inspector Curran is glad to have Harriet's help with this difficult case, but as he seeks to uncover the culprit, his own life begins to unravel. A mysterious man turns up on his doorstep claiming to know more about Curran's past than he himself does. And the one person he has always counted on to be his port in the storm has devastating news that will leave him forever changed. Curran needs Harriet's assistance now more than ever and when another player meets a violent end, she and Curran will have to home in on a killer determined to make this case their final curtain call"--